PERSEPSI PENYULUH AGAMA TENTANG KONFLIK BERBASIS AGAMA (Kasus Ahmadiyah dan Tijani di Kabupaten Sukabumi) - Koeswinarno Koeswinarno; Fakhrudin Fakhrudin (Harmoni, 2013)
The research is aimed at explaining how the religion counselor comprehend the religion-based conflicts in Parakan Salak and Jampan Tengah subdistrict in Sukabumi, West Java. Data collecting technique are through deep interview and FGD to honorary and official servant religion counselor. The result explains that the counselor has good knowledge about anything related to ‘religion’, but is not skilled enough in understanding people’s social structure especially in early detecting social sensitivity. In dealing with a conflict, religion counselor is subordinated to the local religion figure because the counselor does not have direct assignment burden in resolving conflict, as well to the inferiority in doing the assignment is an important factor of how the position of the religion counselor in comprehending conflict is not completely optimal yet. Therefore, a model is needed to grow counselor’s motivation to resolve the conflict.